Analisis Efisiensi Energi pada Sistem Penerangan Gedung Bertingkat - Ahmad Rizky Ramadhan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The increasing electrical energy consumption in high-rise buildings highlights the urgent need for efficient and environmentally friendly lighting systems. This study aims to analyze the energy efficiency level of lighting systems in high-rise buildings through the implementation of energy-saving LED lamps and automated sensor systems. The research methodology involved an energy usage survey, light intensity measurements, and a comparative analysis of energy consumption before and after the implementation of the automation system. The results showed a reduction in energy consumption of up to 35% without compromising users’ visual comfort. The implementation of light and motion sensors also improved operational efficiency and significantly reduced monthly electricity costs. In conclusion, the application of energy-efficient lighting systems has a positive impact on energy sustainability and contributes to reducing carbon emissions in high-rise buildings.